1997
DOI: 10.1080/01688639708403857
|View full text |Cite
|
Sign up to set email alerts
|

Mild head injury and speed of information processing: A prospective study of professional rugby league players

Abstract: The sensitivity of several short tests of speed of information processing to the effects of mild head injury in rugby league football was investigated. The measures used were the Symbol Digit Modalities Test, the Digit Symbol Substitution Test, and the Speed of Comprehension Test. Two studies were conducted, the first to examine the effect of practice, the second to determine sensitivity to cognitive impairment immediately following injury. The first study established alternate form equivalence and demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(61 citation statements)
references
References 18 publications
3
57
1
Order By: Relevance
“…Findings for slowed processing speed and memory are consistent with previous research of acute impairments after non-sport mTBI 9,12,[14][15][16][17] and sports-related concussions. [19][20][21][22][23]25,26,[60][61][62] Impairments in episodic memory and processing speed have been reported in prospective studies that used eligibility criteria similar to the present study, including GCS 13-15 and normal CT scans when available. 15 Our findings confirm these as among the most important cognitive domains to assess after injury from a clinical perspective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings for slowed processing speed and memory are consistent with previous research of acute impairments after non-sport mTBI 9,12,[14][15][16][17] and sports-related concussions. [19][20][21][22][23]25,26,[60][61][62] Impairments in episodic memory and processing speed have been reported in prospective studies that used eligibility criteria similar to the present study, including GCS 13-15 and normal CT scans when available. 15 Our findings confirm these as among the most important cognitive domains to assess after injury from a clinical perspective.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 10 professional rugby players and 10 matched uninjured athletes, Hinton-Bayre and associates 19 found that at 24-48 h post-injury, concussed athletes demonstrated significant dysfunction on the Symbol-Digit Modalities Test (SDMT), Speed of Comprehension, and Digit Span. In a somewhat larger follow-up study, Hinton-Bayre and colleagues 20 essentially replicated their previous findings, but also found that while most players (80%) were impaired 1-3 days post-injury, some players (35%) did not return to baseline performance until 3-5 weeks post-injury.…”
Section: Introductionmentioning
confidence: 99%
“…11,19,20 These instruments included the Standardized Assessment of Concussion, Trail Making Test Part A, Trail Making Test Part B, digit span, Symbol Digit Modalities Test, Hopkins Verbal Learning Test, finger tapping test, and a self-report symptom checklist (Head Injury Scale; Table 1). [21][22][23][24][25][26] All tests were administered in the same order to decrease test effects during neuropsychological assessment. Although numerous assessment batteries are available, we chose this traditional pencil-and-paper neuropsychological test battery due to its extensive use in research and age appropriateness of tests.…”
Section: Neuropsychological Batterymentioning
confidence: 99%
“…SCOLP is originally a written test that provides a measure of the slowing down of cognitive processing following mild head injury (Hinton-Bayre et al 1997). In SCOLP, the participant verifies as many sentences as possible in two minutes.…”
Section: Introductionmentioning
confidence: 99%